Harmful Health Impacts of Heavy Metals and Behavioral Changes in Humans - Baig, Ayesha; Sial, Shehzad Ahmad; Qasim, Muhammad; Ghaffar, Aisha; Ullah, Qudrat; Haider, Sameea; Fatima, Shamaim; Shawal, Laila; Ather, Nimra (PT FORMOSA CENDEKIA GLOBAL, 2024)
Heavy metal pollution not only affects the environment but also the behavior of people who are greatly dependent on their surrounding environment for their survival. There are both natural and anthropogenic sources of heavy metals but their pollution by manmade activities are quite faster than natural sources. A person gets exposed to heavy metals by four major exposure pathways i.e. inhalation, ingestion, dermal exposure and injection. After exposure to heavy metals, internal normal body functions of an individual gets disturbed. This in turn alters the human behavior from normal to an abnormal state. Various behavioral changes are associated with heavy metals exposure such as depression, anxiety, irregular heartbeats, stress, decrease in strength and power, lack of confidence, restlessness, lack of tolerance and aggressions among the individuals and the society as a whole. This review entails the information regarding sources of heavy metals, exposure pathways and health effects of heavy metals resulting in behavioral changes in humans.